Analisis Saluran Pemasaran Semangka (Citrullus Lanatus) Di Desa Paya Itik Kecamatan Galang Kabupaten Deli Serdang - Fauzi, Rahmad; Kuswardani, Retna Astuti; Salqaura, Siti Sabrina (Universitas Medan Area, 2025)
This study aims to analyze the marketing channels and efficiency of watermelon marketing in Paya Itik Village, Galang District, Deli Serdang Regency. The research location was chosen purposively, with watermelon farmers selected using purposive sampling, while marketing institutions were chosen using snowball sampling. Data were analyzed using both qualitative and quantitative descriptive methods. Qualitative descriptive analysis was used to examine the marketing channels, while quantitative analysis was employed to calculate marketing margins, farmer’s share, and marketing efficiency. The results identified three marketing channels, with the third channel having the highest marketing margin, while the first channel provided the highest farmer’s share. In terms of efficiency, marketing channels I and II for grade A watermelons were considered efficient, with marketing efficiency between 0-33%. This study offers insights into efficient watermelon marketing patterns and has the potential to help farmers improve profitability by optimizing their choice of marketing channels.